Quantification of extracrystalline acid sites in MFI zeolites after post-synthetic passivation treatments using mesitylene benzylation kinetics - Ezenwa S; Hopping GM; Sauer ED; Scott T; Mack S; Gounder R (Royal Society of Chemistry, 2024)
Brønsted acid sites (H+) located at extracrystalline surfaces of zeolites influence catalyst reactivity, selectivity, and deactivation behavior. The number of extracrystalline H+ sites is difficult to quantify reliably using spectroscopic or titrimetric techniques when present in dilute quantities, such as after post-synthetic surface passivation treatments. Here, methods to quantify extracrystalline H+ sites on MFI zeolites were developed by measuring the kinetics of mesitylene benzylation with dibenzyl ether to form 1,3,5-trimethyl-2-benzylbenzene, which is sterically prevented from forming at intracrystalline H+ sites within microporous voids. These methods were applied to investigate MFI zeolite samples that were systematically treated using ammonium hexafluorosilicate (AHFS) with varying treatment durations, AHFS concentrations, and numbers of successive treatment cycles. Rates of mesitylene benzylation with dibenzyl ether (363 K) were measured on a suite of MFI samples with known amounts of external H+ sites (0.01-0.15 H+ext/Al), quantified by 2,6-di-tertbutylpyridine titration, to determine the intrinsic zero-order rate constant for mesitylene benzylation (per H+ext). Quantification of zero-order rate constants on post-synthetically treated MFI zeolites shows that AHFS treatments selectively passivate extracrystalline H+ sites with efficacies that depend on the specific treatment conditions used. The kinetic methods developed here enable quantifying extracrystalline acid sites in amounts below the detection limits of common spectroscopic and titration techniques on various small-pore and medium-pore zeolites, enabling assessments of the efficacy of post-synthetic surface passivation treatments and rigorous evaluation of the reactivity of extracrystalline H+ sites during acid catalysis.